MEDIA PEMBELAJARAN AUDIO-VISUAL UNTUK MENINGKATKAN MOTIVASI DAN KETERAMPILAN BERPIKIR KRITIS SISWA DENGAN PENDEKATAN SCIENTIFIC - Made Prima Restami; Muhamad Samsudin (STKIP PGRI Situbondo, 2023)
This research originated from a problem that occurred in the field: the implementation of physics learning was not optimal, which still refers to a low-level thinking model so that critical thinking skills in students are poorly trained. Therefore, teachers are led to be more professional and choose to use media that is in accordance with the material to be taught so that the teaching and learning process will be more effective and meaningful. One of the learning media tried in this study is audio-visual learning media with a scientific approach. This study aims to determine the effect of using audio-visual learning media with a scientific approach on achieving learning motivation and critical thinking skills in class X SMA Negeri 3 Singaraja in physics. This study takes a quantitative approach with quasi-experimental research and a pretest and posttest control group design. The research population was class X students, consisting of 5 classes with a total of 190 people, and the sample in class X2 was 40 people as the experimental class and class X3 with 40 people as the control class. The techniques used for data collection are questionnaires and tests. The research shows that there are differences in critical thinking skills before and after being given treatment. The Anacova test and t-test results with a significance value of 0.000 indicate that the sig value is 0.05 and the Pearson correlation (t) is 0.861. so that H0 is rejected and Ha is accepted. So it can be concluded that there is an influence of users of audio-visual learning media with a scientific approach on students' learning motivation and critical thinking skills, and there is a correlation between learning motivation and critical thinking skills in physics subjects at SMA Negeri 3 Singaraja.